Hydrostatic bearing design selection for automotive application using pugh controlled convergence method - Seperamaniam, Thandayuthapani; Abdul Jalil, Nawal Aswan; Zulkefli, Zamir Aimaduddin (Elsevier, 2017)
This paper evaluates the design selection of a hydrostatic bearing pad for automotive application. The purpose of hydrostatic bearing is to eliminate high frequency vibration from gear mesh-frequency, example from heavy truck. Pugh controlled convergence method was used to obtain the optimum design shape for selection. The setting up parameter criteria verses the concept pad shape between applications of hydrostatic journal and hydrostatic thrust bearings were varied. Comparison of design engineering criteria was made with number of leading concepts in hydrostatic bearing for ultimate qualitative optimization, and the parameter design criteria was customized for automotive heavy truck vehicle. Fourteen (14) selection considerations were used as, manufacturing ease, safety of the design, cost development, accuracy in output, reliability in life span, simplicity in degree of design, load capacity, stiffness, damping, suppress temperature rise, pumping power, mounting space for fitting, oil circulation without leakage and finally displacement of the controlled plunger. From this convergence method,‘Circular recess pocket plunger’ with spring loaded (CRPP) conceptually selected. It was model from qualitative optimization by combining ‘squeeze film damper’ (SFD) of a journal bearing without journal rotation and Cooper's squeeze film coil spring test apparatus.